Polycrystalline metal-organic framework (MOF) membranes for molecular separations: Engineering prospects and challenges - Abdul Hamid, Mohamad Rezi; Qian, Yutian; Wei, Ruicong; Li, Zhen; Pan, Yichang; Lai, Zhiping; Jeong, Hae-Kwon (Journal of membrane science, 2021)
Metal-organic frameworks (MOFs), owing to their ordered porous structure, ease of synthesis, and versatility of surface functionalization have attracted significant research interests for membrane-based separations. Zeolitic-imidazolate frameworks (ZIFs), a subclass of MOFs, have drawn the most research attention by virtue of their ease of forming high-quality membranes and potential in hydrocarbon mixture separations. Other MOF-based membranes such as IRMOFs, HKUST-1, MILs, UiOs, etc., were also well-studied for hydrogen purification and carbon capture. In this review, we summarize a chronological development of MOF membranes for gas separations, focusing on ZIF-8 membranes for C3H6/C3H8 separation. Other MOF membranes for H2/CO2, CO2/CH4, and CO2/N2 separations are also reviewed. Following this, we provide a thorough assessment and evaluation of the engineering challenges, including cost-effectiveness, module design, and membrane stability and reproducibility for industrial scale-up. Finally, we provide our point of view on future research and development in the area. [Display omitted] •Chronological development of MOF membranes for gas separations was reviewed.•MOF membrane separations are based on kinetic and thermodynamic effects.•Hybrid MOF approaches enable tuning of MOF transport properties.•Post-synthetic modifications are effective to improve membrane performances.•Transitioning MOF membranes from laboratory to industry is not trivial.